(untitled) (Baltic Journal of Sport and Health Sciences, 2014)
Background. Intellectual disability is defined as significantly reduced ability to understand new or complex information, to learn and to apply new skills. Integration into the society and independent living for intellectually disabled people is demanding because of slowdown decision processing. Quick enough response time is of vital importance not only for the motor development but also for faster and better adaptation to the changing life conditions. Methods. The subjects were 112 persons with and without intellectual disability aged 11 to 18 years and recruited for the study. The Reaction Timer RA-1 was used to measure reaction time and to determine the speed characteristics of the person’s psychomotor response before and after moderate intensity exercising. Heart rate monitor Polar RS800 was used to measure the person’s heart rate. Results. The best reaction time was demonstrated by 16-year-old normally developed individuals and those with mild intellectual disability (p < .05). The slowest were 11 and 12-year-old individuals (p < .05). The best reaction time was demonstrated by 14-year-old individuals with moderate intellectual disability and the worst – by 12 and 16 year-old persons with this disability (p < .05). Conclusion. Moderate-intensity exercising has a positive influence on the execution of the complex reaction task (LRHL). The considerable reaction time increase was observed for individuals with moderate intellectual disability. Keywords: intellectual disability, reaction time, moderate intensity exercising.